Path coefficient analysis of seed yield in coriander (Coriandrum sativum L.). (Indian Journal of Arid Horticulture, 2016)
Path analysis evaluation of 45 genotypes of coriander (Coriandrum sativum L.) at Mandsaur (Madhya Pradesh)indicated that seeds umbel-I had the highest positive direct effect on seed yield per plant at phenotypic as well as genotypiclevel. At both genotypic and phenotypic level, the highest positive indirect effect on seed yield was exerted by test weight viaseeds umber1 followed by umbellet umber1 via seeds umber1• While the highest negative indirect effect on seed yield wasimposed by days to 50 percent flowering via seeds umber1 followed by oil percent in seeds via seeds umber1. So pathcoefficient analysis revealed that seeds umber1, test weight, umbellet umber1 and early flowering were the most importantcharacters for selection in coriander genotypes.
Keywords: coriander; direct effect; indirect effect; Path coefficient; seed yield